A systematic way of achieving Total Continuous Process Improvement (TCPI) in an industry - Khoo, Michael B.C.; Ch'ng, C.K. (2004)
This paper highlights the steps that are required to achieve total continuous process improvement in the production of products in a manufacturing industry. The importance of each step will be discussed and the strategies that need to be taken to achieve the objectives of each of the steps will be mentioned. The aim of this paper is to provide essential guidelines for operators, supervisors, engineers and managers so that they are aware of the various steps that need to be taken in achieving TCPI.